Baile Charme de Madureira e o processo de patrimonialização de natureza imaterial no Rio de Janeiro - Cruz, Luciana Mota da (2017)
The purpose of this dissertation is to investigate the process of legitimating the title of intangible cultural heritage of the city of Rio de Janeiro, attributed to the Baile Charme in 2013 (Decree 36803/13). The Baile Charme is an event held twenty-seven years ago under the Negrão de Lima viaduct, in the neighborhood of Madureira, in the city’s north zone. Through the analysis of interviews with the agents responsible for the creation, organization and legitimation of Baile Charme, this research intends to examine the origins of this event, as well as the social agents involved in it, the territories occupied by the charmers to finally try to understand why Baile Charme was registered as intangible cultural heritage, but its effective recognition has not yet been occurred. For all points raised, it is also intended to offer a contribution that can be used in the recognition of the Baile Charme as intangible cultural heritage of the city of Rio de Janeiro.